Studi Metaanalisis: Hubungan Antara Kecerdasan Emosional dan Kecenderungan Perilaku Cyberbullying - Aqmal Maulana Saputra; Muhammad Bintang Fadillah (Humanitas (Jurnal Psikologi), 2024)
Along with the rapid development of technology, the phenomenon of cyberbullying is massive and alarming. This study aims to produce metaanalysis findings on previous research related to the relationship between emotional intelligence and cyberbullying. As an analysis material, the author used 10 published scientific journals relevant to the research topic. The analysis was conducted using JASP (Jeffrey's Amazing Statistics Program) software version 0.18.1. Hypothesis testing results showed a significant negative correlation between emotional intelligence and cyberbullying behavior, with a p value <0.001. Fixed and Random Effects analysis resulted in a Chi-Square value of 102.342 with df 1 (p < 0.001). The residual heterogeneity test resulted in significant variation between study results, with a Q-value of 234.187 and df of 9 (p < 0.001). Analysis of possible publication bias showed a negative correlation in Funnel Plot Asymmetry (Kendall's τ = -0.333, p = 0.216), but without sufficient evidence to reject the null hypothesis. The results of Fail-safe N of 22022 > 5(10) + 10 show that this meta-analysis research does not have publication bias. It is necessary to add 22022 studies that are not significant or have not been published to this meta-analysis so that the overall results of the observations become statistically insignificant.